9.1% efficient zinc oxide/silicon solar cells on a 50 μm thick Si absorber - Pietruszka, Rafal; Witkowski, Bartlomiej S.; Ozga, Monika; Gwozdz, Katarzyna; Placzek-Popko, Ewa; Godlewski, Marek (Beilstein Journal of Nanotechnology, 2021)
Today, silicon solar cells (amorphous films and wafer-based) are a main source of green energy. These cells and their components are produced by employing various technologies. Unfortunately, during the production process, chemicals that are harmful for the environment and for human life are used. For example, hydrofluoric acid is used to texture the top electrode to improve light harvesting. In this work, and also in recent ones, we report a way to obtain 3D textures on the top electrode by using zinc oxide nanorods. The efficiency of a textured solar cell structure is compared with the one obtained for a planar zinc oxide/silicon structure. The present results show the possibility to produce efficient solar cells on a relatively thin 50 μm thick silicon substrate. Solar cells with structured top electrodes were examined by numerous measuring techniques. Scanning electron microscopy revealed a grain-like morphology of the magnesium-doped zinc oxide film. The size of the grains is closely related to the structure of the nanorods. The external quantum efficiency of the cells was measured. The obtained solar cell shows response in a wide spectral range from ultraviolet to infrared. Current–voltage and current–voltage–temperature measurements were performed to evaluate basic photovoltaic parameters. At room temperature, the cells efficiency equals to 9.1% for textured structures and 5.4% for planar structures, respectively. The work, therefore, describes an environmentally friendly technology for PV architecture with surface textures increasing the efficiency of PV cells.
Keywords: atomic layer deposition; hydrothermal method; photovoltaics; silicon; solar cell; zinc oxide